Imitation in heterogeneous populations - Hedlund, Jonas; Oyarzun, Carlos (Economic theory, 2018)
We study a boundedly rational model of imitation when payoff distributions of actions differ across types of individuals. Individuals observe others’ actions and payoffs, and a comparison signal. One of two inefficiencies always arises: (i) uniform adoption, i.e., all individuals choose the action that is optimal for one type but suboptimal for the other, or (ii) dual incomplete learning, i.e., only a fraction of each type chooses its optimal action. Which one occurs depends on the composition of the populations and how critical the choice is for different types of individuals. In an application, we show that a monopolist serving a populations of boundedly rational consumers cannot fully extract the surplus of high-valuation consumers, but can sell to consumers who do not value the good.